2002
DOI: 10.1071/rd01046
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotrophic hormone (ACTH) stimulation of sheep fetal adrenal cortex can occur without increased expression of ACTH receptor (ACTH-R) mRNA

Abstract: In the present study, it was hypothesized that the adrenocorticotrophin hormone receptor (ACTH-R) would be up-regulated in the adrenal gland of the sheep fetus following infusion of physiological amounts of ACTH, as shown for adrenal cortical cells in culture. In chronically catheterized sheep, an intravenous infusion of ACTH(1-24) was given to 6 fetuses for 24 h at a rate of 0.5 microg h(-1), starting on Day 126 or 127 of gestation (term approximately 147 days). Four control fetuses received an infusion of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Considering the above, it is surprising that there are two reports that ACTH-(1-24) infusions in fetal sheep do not change ACTH-R mRNA levels (3,25). This may be due to changes in mRNA levels below the assay detection level (25) or doses of ACTH below the threshold for producing an effect on receptor expression.…”
Section: Discussionmentioning
confidence: 82%
“…Considering the above, it is surprising that there are two reports that ACTH-(1-24) infusions in fetal sheep do not change ACTH-R mRNA levels (3,25). This may be due to changes in mRNA levels below the assay detection level (25) or doses of ACTH below the threshold for producing an effect on receptor expression.…”
Section: Discussionmentioning
confidence: 82%
“…Signals from ACTH are transduced via activation of ACTHR. Previous studies have shown that in sheep, ACTH does not increase fetal adrenal ACTHR mRNA levels 36,37 ; however, other authors have demonstrated a progressive increase in ACTHR mRNA in mid-to late gestation ovine fetal adrenals. 25 This has been confirmed by a more recent publication using different methods of analysis and different doses of ACTH, which also showed a linear relationship between fetal plasma ACTH concentration and receptor mRNA levels, 26 indicating the importance of using more sensitive techniques.…”
Section: Discussionmentioning
confidence: 92%
“…Total RNA from sheep adrenal gland (1 μ g) was used as a template for reverse transcription using protocols exactly as described (Carter et al. 2002).…”
Section: Isolation Of Rna From Sheep Organs and Reverse Transcriptionmentioning
confidence: 99%
“…PCR was performed exactly as described (Carter et al. 2002) for 35 cycles consisting of denaturation for 30 s, annealing (45 s at 56 °C), and primer extension (45 s at 72 °C).…”
Section: Isolation Of Rna From Sheep Organs and Reverse Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation